Buddhist women and social justice : ideals, challenges, and achievements - Karma Lekshe Tsomo, 1944- (SUNY series, feminist philosophy., 2004)
"This book on engaged Buddhism focuses on women working for social justice in a wide range of Buddhist traditions and societies. Contributors document attempts to actualize Buddhism's liberating ideals of personal growth and social transformation. Dealing with issues such as human rights, gender-based violence, prostitution, and the role of Buddhist nuns, the work illuminates the possibilities for positive change that are available to those with limited power and resources. Integrating social realities and theoretical perspectives, the work utilizes feminist interpretations of Buddhist values and looks at culturally appropriate means of instigating change."--Jacket